AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (STUDI KASUS PENGELOLAAN ALOKASI DANA DESA DI DESA WIJIREJO KECAMATAN PANDAK -KABUPATEN BANTUL TAHUN 2016/2017) - Rigel Nurul Fathah (Universitas Muhammadiyah Jember, 2017)
Abstract: This research focuses on the application of the principle of accountability on the management of the Village Fund Allocation of describing the management accountability Village Fund Allocation. This research will be conducted because Allocation Fund Executive Team Village in performing its financial expected to be beneficial to Wijirejo village government in an effort to increase management accountability Village Fund Allocation.This research will conducted in village in the subdistrict Pandak, as one implementation location of the Village Fund Allocation. As the informants was elected Village Implementation Teams and the communities that are considered to represent the research unit in the management of the Village Fund Allocation.The results of this study indicate that for the planning and implementation activities of the Village Fund Allocation, has revealed the existence of management accountable and transparent. While accountability is seen in the physical results have shown the implementation of accountable and transparent, but from the administration still needed further development, because not fully in accordance with the provisions. The main constraint is not effective coaching village government officials and human resource competencies, so that still need assistance from local government officials on an ongoing basis .Keywords: Allocation Fund Village, Accountability, Transparency